Solvent-terminated dispersive liquid-liquid microextraction: a tutorial - Mansour, Fotouh R.; Danielson, Neil D. (Analytica chimica acta, 2018)
Solvent-terminated dispersive liquid-liquid microextraction (ST-DLLME) is a special mode of DLLME in which a demulsifying solvent is injected into the cloudy mixture of sample/extractant to break the emulsion and induce phase separation. The demulsification process starts by flocculation of the dispersed microdroplets by Ostwald ripening or coalescence to form larger droplets. Then, the extractant either floats or sinks depending on its density as compared with that for the aqueous sample. The demulsifier should have high surface activity and low surface tension in order to be capable of inducing phase separation. The extraction efficiency in ST-DLLME is controlled by the same experimental variables of normal DLLME (n-DLLME) such as the type and volume of the extractant as well as the disperser. Other parameters such as pH and the temperature of the sample, the stirring rate, the time of extraction and the addition of salt are also important to consider. Along with these factors, the demulsifier type and volume and the demulsification time have to be optimized. By using solvents to terminate the dispersion step in DLLME, the centrifugation process is not necessary. This in turn improves precision, increases throughput, decreases the risk of contamination through human intervention and minimizes the overall analysis time. ST-DLLME has been successfully applied for determination of both inorganic and organic analytes including pesticides and pharmaceuticals in water and biological fluids. Demulsification via solvent injection rather than centrifugation saves energy and makes ST-DLLME easier to automate. These characteristics in addition to the low solvent consumption, the reduced organic waste and the possibility of using water in demulsification bestow green features on ST-DLLME. This tutorial discusses the principle, the practical aspects and the different applications of ST-DLLME. [Display omitted] •A remarkable progress of ST-DLLME has been observed in the last few years.•The demulsifier type and volume and the demulsification time control the extraction efficiency in ST-DLLME.•The different applications of ST-DLLME and the green aspects of this new mode have also been discussed.